Answer:
Step-by-step explanation:
[tex]7-8x=7(1+7x)\qquad\text{use the distribtutive property}\ a(b+c)=ab+ac\\\\7-8x=(7)(1)+(7)(7x)\\\\7-8x=7+49x\qquad\text{subtract 7 from both sides}\\\\-8x=49x\qquad\text{subtract}\ 49x\ \text{from both sides}\\\\-57x=0\qquad\text{divide both sides by (-57)}\\\\x=0[/tex]
Answer:
x = 0
Step-by-step explanation:
Given
7 - 8x = 7(1 + 7x) ← distribute parenthesis
7 - 8x = 7 + 49 x ( subtract 49x from both sides )
7 - 57x = 7 ( subtract 7 from both sides )
- 57x = 0 ⇒ x = 0